2022
DOI: 10.1097/jsm.0000000000001030
|View full text |Cite
|
Sign up to set email alerts
|

Concussion-Associated Gene Variant COMT rs4680 Is Associated With Elite Rugby Athlete Status

Abstract: Concussions are common match injuries in elite rugby and reports exist of reduced cognitive function and long-term health consequences that can interrupt or end a playing career and produce continued ill health. The aim of this study was to investigate the association between elite rugby status and eight concussion-associated risk polymorphisms. We hypothesized that concussion-associated risk genotypes and alleles would be underrepresented in elite rugby athletes compared to non-athletes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 68 publications
0
11
0
Order By: Relevance
“…We separately found no differences in genotype frequencies between elite rugby athletes and non-athletes for seven out of eight concussion-associated genetic variants [34]. That might have been because individual variants cannot represent the complexity of concussion risk and do not reflect SNP-SNP interactions, known as non-linear interaction or epistasis [53].…”
Section: Discussionmentioning
confidence: 69%
See 4 more Smart Citations
“…We separately found no differences in genotype frequencies between elite rugby athletes and non-athletes for seven out of eight concussion-associated genetic variants [34]. That might have been because individual variants cannot represent the complexity of concussion risk and do not reflect SNP-SNP interactions, known as non-linear interaction or epistasis [53].…”
Section: Discussionmentioning
confidence: 69%
“…Lipsky et al [23] observed that GG carriers had 40% poorer executive function than AA carriers post-TBI. Recently, it has been observed that elite rugby athletes have 1.4 times the odds of possessing the GG genotype of COMT (rs4680) compared to non-athletes [34]. In addition, Mc Fie et al [33] observed that A allele carriers in a cohort of youth and professional South African RU players were approximately more likely to have a history of concussion.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations